Driven Towards Death – A Psychoanalysis Approach In Interpreting The Novel Kokoro By Natsumi Soseki - Jordan Marelino Parsaulian Naibaho; Mike Wijaya Saragih (Universitas Cokroaminoto Palopo, 2023)
This paper aims to attest the author's interpretation that Sensei's character in the novel